Relationships between circulating branched chain amino acid concentrations and risk of adverse cardiovascular events in patients with STEMI treated with PCI. Issue 1 (December 2018) - Du, Xiaoyu; You, Hongzhao; Li, Yulin; Wang, Yuan; Hui, Peng; Qiao, Bokang; Lu, Jie; Zhang, Weihua; Zhou, Shanshan; Zheng, Yang; Du, Jie
Abstract The incidence of in-hospital cardiovascular adverse events (AEs) in patients with ST-segment elevation myocardial infarction (STEMI) following primary percutaneous coronary intervention (PCI) is relatively high. Identification of metabolic markers could improve our understanding of the underlying pathological changes in these patients. We aimed to identify associations between concentrations of plasma metabolites on admission and development of in-hospital AEs in post-PCI patients with STEMI. We used targeted mass spectrometry to measure plasma concentrations of 26 amino acid metabolites on admission in 96 patients with STEMI who subsequently developed post-PCI AEs and in 96 age- and sex-matched patients without post-PCI cardiovascular AEs. Principal component analysis (PCA) revealed that PCA-derived factors, including branched chain amino acids (BCAAs), were associated with increased risks of all three pre-specified outcomes: cardiovascular mortality/acute heart failure (AHF), cardiovascular mortality, and AHF. Addition of BCAA to the Global Registry of Acute Coronary Events risk score increased the concordance C statistic from 0.702 to 0.814 (p < 0.001), and had a net reclassification index of 0.729 (95% confidence interval, 0.466–0.992, p < 0.001). These findings demonstrate that high circulating BCAA concentrations on admission are associated with subsequent in-hospital AEs after revascularization in patients with STEMI.